Crescimento inicial de espécies arbóreas em substrato impacto por resíduo industrial alcalino rico em zinco - Ygor Maximiliano de Pompein Pessoa (2010)
xivAbstractThe industrial production of zinc alloys generates large amounts of chemical waste. An areaof approximately 16 hectares previously designed for the reception of industrial waste wasselected as a target for an environmental recovery project, objective of this work. The resultsshowed a significant difference between the control and contaminated soil due to high pH,lower microbial biomass and reduced concentration of organic matter, phosphorus andnitrogen. From floristic and phytosociological studies adjacent to the impacted area, eight treespecies were selected for use in vegetation restoration project. The resilience and adaptabilityto the conditions of the degraded area was analized by experiment in a greenhouse, whichevaluated the growth of the respective species for 120 days in pots containing thecontaminated soil, with subsequent addition of chemical fertilizer, organic substrate andarbuscular mycorrhizal fungi spores extracted from an uncontaminated control area. Amongthe tested species, Astronium fraxinifolium Schott (Gonçalo Alves), Peltophorum dubiumSpreng. (Canafístula) e, Dipteryx alata Vogel (Baru) were very sensitive to the contaminatedsoil due to the high mortality of plants. Copaifera Desf. (Copaíba) e Hymenaea stignocarpaMart. (Jatobá do Cerrado), despite registering a high survival rate, have not properlydeveloped in contaminated soil. Enterolobium contortisiliquum (Vell.) Morong (Tamboril),Tamarindus indica L. (Tamarindo) e Tabebuia ochraceae (Cham.) Standl. (Ipê amarelo doCerrado), presented high survival and proper development of species, particularly intreatments with organic substrate. Overall, the use of organic matter added to soil assigned theability to mitigate the impact in all tested species. The organic substrate derived fromearthworm castings, compost litter and manure demonstrated, respectively, the best organiccomplement for the contaminated soil for Tamboril. We detected a rate of colonization ofroots by mycorrhizal fungi greater than 50% in species subjected to the treatments inoculatedwith spores. Leaf concentrations of phosphorus and zinc were determined and, in general, theproposed treatments to mitigate the impact of degraded soil in the area provided a higheramount of phosphorus in the leaves of the evaluated species. There were no highconcentration of zinc in the leaves. It was recommended the planting of Ipe, Tamboril andTamarindo, associated with the use of additional organic matter and mycorrhizal inoculationwith spores, for revegetation of the degraded area and other areas whose disruption in thephysical, chemical and biological soil are similar to the area of study.